Acute kidney injury in intensive care unit: what are parameters of recovery? - Alshaimaa S. Mubarak; Hanan Sharaf EL-Deen; Marwa K. Khairallah; Mohamed Mongy Zayed; Naglaa Mohamed M. A. Mousa; Dina Ali Hamad (The Egyptian Journal of Internal Medicine, 2026)
Abstract Background Acute Kidney Injury(AKI) is a sudden decline in kidney function, commonly occurring in critically ill patients due to factors such as sepsis, surgery, or inflammation. Management includes supportive care and, when necessary, renal replacement therapy(RRT). Outcomes range from complete recovery to chronic kidney impairment. Aim To detect the factors which influence the recovery time of AKI in critically ill patients in the ICU. Methods This is a prospective observational cohort study that included 154 patients admitted to the ICU of Assiut University Hospital between December 2023 and December 2025, and only the first AKI episode was analyzed. Clinical data, comorbidities and labs(renal/liver function, blood counts, CRP, blood gases) were documented and renal monitored hourly. Recovery was defined as either creatinine normalization or RRT cessation, and was grouped by time:1–2, 3–4, 5–7,>7 days. Results Mean age was 51 ± 15.11 years; 46.1% male. Comorbidities were present in 77.9%, the most common being diabetes(26%), hypertension(18%) and CKD(18%). AKI was mostly renal(65.6%), with stages 1,2, and 3 at 28.6%,34.4%, and 37.0%. Renal recovery was achieved in 93.5%(median 4.5 days), 13.6% needed hemodialysis and the median duration of stay in the ICU was 7 days. Older age, higher BMI, comorbidities, lower hemoglobin/albumin, higher CRP and worse baseline renal function were all associated with poor recovery. Comorbidities, hemoglobin, albumin, and baseline creatinine were independent predictors. Conclusion Comorbidities, low hemoglobin/albumin, and severe AKI were linked to delayed renal recovery, while early AKI and better baseline health predicted better outcomes. Early recognition and prompt management may improve recovery.